466 Influence of Race on Early Outcomes of Elective Lumbar Interbody Fusions: An Updated Propensity-Matched and Subgroup Analysis. (1st April 2022) - Alomari, Safwan; Porras, Jose L.; Jud, Brendan F.; Witham, Timothy F.; Bydon, Ali
Abstract : INTRODUCTION: Several studies have consistently found that black patients, when compared to white patients, were more likely to have postoperative morbidity and mortality. However, these studies have several limitations. METHODS: Patients who underwent (PLIF/TLIF) or (ALIF/LLIF) between 2015-2018 were reviewed from ACS-NSQIP database. Propensity score matching and subgroup (single/multi-level) analysis were used RESULTS: 17, 471 PLIF/TLIF cases and 8, 760 ALIF/LLIF cases met inclusion criteria and were reviewed. In both single/multi-level PLIF/TLIF and ALIF/LLIF, black patients were more likely to be younger, have higher BMI, be of female gender, have inpatient admission status, have an ASA class 3 or more, be a smoker, have baseline dyspnea, have hypertension and be functionally dependent. In both single/multi-level ALIF/LLIF, black patients were more likely to have diabetes mellitus. In both groups (single/multi-level PLIF/TLIF and ALIF/LLIF), except for the higher incidence of DVT in the black cohort, there were no significant differences in morbidity and mortality measures between the black and white cohorts. CONCLUSION: In contrast to prior literature, our analysis did not identify black race as an independent risk factor for higher perioperative morbidity or mortality in patients undergoing elective lumbar fusion, except for the higher incidence of venous thromboembolism. The findings of the present study are important for clinicians and spine surgeons while counseling patients undergoing these types of procedures. It is important to address patient's concerns and to explain that the previously reported inferior perioperative morbidity and mortality outcomes in black patients might be due differences in baseline health status, and not due to the race difference itself.